The effect of recreational cannabis legalization on rates of traffic injury in Canada. - Walker, Madison; Saarela, Olli; Mann, Robert; Carpino, Melissa; Cusimano, Michael D (Addiction, 2023)
AIMS: To measure the impact of Canada's recreational cannabis legalization (RCL) in October 2018 and the subsequent impact of the COVID-19 lockdowns from March 2020 on rates of emergency department (ED) visits and hospitalizations for traffic injury. DESIGN: An interrupted time series analysis of rates of ED visits and hospitalizations in Canada recorded in population-based databases from January/April 2010 to March 2021. SETTING: ED visits in Ontario and Alberta and hospitalizations in Ontario, Alberta, British Columbia, Prairies [Manitoba, Saskatchewan], and Maritimes [Nova Scotia, New Brunswick, Newfoundland, Prince Edward Island]. Cases Monthly counts of presentations to the ED or hospital for motor vehicle injury or pedestrian/cyclist injury, used to calculate monthly rates per 100,000 population. MEASUREMENTS: An occurrence of one or more International Statistical Classification of Diseases and Related Health Problems, 10th Revision, Canada (ICD-10-CA) code for motor vehicle injury (V20-V29, V40-V79, V30-39, V86) and pedestrian/cyclist injury (V01-V09, V10-V19) within the National Ambulatory Care Reporting System and Discharge Abstract Database. FINDINGS: There were no statistically significant changes in rates of ED visits and hospitalizations for motor vehicle or pedestrian/cyclist injury after RCL after accounting for multiple testing. After COVID-19, there was an immediate decrease in the rate of ED visits for motor vehicle injury that was statistically significant only in Ontario (level change ß = -16.07 in Ontario, 95% confidence interval [CI] -20.55 to -11.60, p=0.000; ß = -10.34 in Alberta, 95% CI -17.80 to -2.89, p=0.008; alpha of 0.004) and no changes in rates of hospitalizations. CONCLUSIONS: Canada's recreational cannabis legalization (RCL) did not notably impact motor vehicle and pedestrian/cyclist injury. The rate of emergency department visits for motor vehicle injury decreased immediately after COVID-19, resulting in rates below post-RCL levels in the year after COVID-19.